2020
DOI: 10.1080/14494035.2020.1769275
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to collaborative performance: examining the different combinations of conditions under which collaborations are successful

Abstract: The literature on collaborative governance has generated several comprehensive models detailing the conditions which collaborations must meet to achieve collaborative performance. The importance of each separate conditionsuch as the presence of incentives to participate, appropriate institutional designs, or facilitative leadershiphas been validated in various studies. How all of these conditions interact with each other, and whether all of the conditions need to be present to achieve performance, is less well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…Finally, most CGRs meet on a quarterly to monthly basis or a quarterly basis, though some meet annually to quarterly or more than monthly, and very few meet less than annually. Overall, these findings provide descriptive evidence about key attributes of collaborative governance explored in the literature, including the leadership role of collaborative participants as convener and facilitator (Ansell & Gash, 2008;Emerson et al, 2009;Heikkila & Gerlak, 2005;Ulibarri, 2015b), role and size of staff and human capital (Hamilton & Lubell, 2018;Leach & Pelkey, 2001;Mosley, 2012;Scott, 2016a;Ulibarri, 2015b), and deliberation in face-to-face meetings (Biddle, 2017;Douglas et al, 2020;Scott, 2016b;Ulibarri, 2015aUlibarri, , p. 2015.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Finally, most CGRs meet on a quarterly to monthly basis or a quarterly basis, though some meet annually to quarterly or more than monthly, and very few meet less than annually. Overall, these findings provide descriptive evidence about key attributes of collaborative governance explored in the literature, including the leadership role of collaborative participants as convener and facilitator (Ansell & Gash, 2008;Emerson et al, 2009;Heikkila & Gerlak, 2005;Ulibarri, 2015b), role and size of staff and human capital (Hamilton & Lubell, 2018;Leach & Pelkey, 2001;Mosley, 2012;Scott, 2016a;Ulibarri, 2015b), and deliberation in face-to-face meetings (Biddle, 2017;Douglas et al, 2020;Scott, 2016b;Ulibarri, 2015aUlibarri, , p. 2015.…”
Section: Discussionmentioning
confidence: 84%
“…In this section, we analyze multiple CGR characteristics noted in the literature, including organizational form, lead organization, funding model, structural roles, staffing, and the extent of face-to-face meetings (e.g., Biddle, 2017;Clarke, 2017;Douglas et al, 2020;Mosley, 2012;Scott, 2016aScott, , p. 2016Ulibarri, 2015aUlibarri, , p. 2015.…”
Section: Collaborative Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative governance is defined as "processes and structures of public policy decision making and management that engage people constructively across the boundaries of public agencies (…) in order to carry out a public purpose that could not otherwise be accomplished" (Emerson et al 2012, p.2). Recent efforts to follow the trajectories of several collaborative governance initiatives have been possible through the analysis of the Collaborative Governance Case Databank (Douglas et al 2020b). Key factors for successful collaborations include having strong incentives to join the collaboration, as well as achieving a high degree of institutionalization in the collaborative process (Douglas et al 2020a).…”
Section: Collaborative Governance Over Timementioning
confidence: 99%
“…In fact, there have been several attempts to understand how individuals' role identities have an impact on public and private organizations over time but not on collaborative governance processes (Brower and Abolafia 1997;Ramarajan 2014;Kobarg et al 2017;Luu et al 2018;Tempelaar and Rosenkranz 2019;Mu et al 2020). Moreover, while there have been recent efforts to disentangle collaborative governance processes throughout their life cycle (Douglas et al 2020a;Douglas et al 2020b;Torfing et al 2020;Ulibarri et al 2020), it is still unclear how individuals' roles affect their identities and collaborative performance, particularly when individual participants in civil service have transitioned between roles, departments, and organizations during the life cycle of the collaboration. Based on the research gap identified above, the research question is: How do participants' role identity and transition style influence collaborative performance along the collaborative life cycle?…”
Section: Introductionmentioning
confidence: 99%